Numerical Investigation of Droplet Properties of a Liquid Jet in Supersonic Crossflow - Yu-Qi Wang; Feng Xiao; Sen Lin; Yao-Zhi Zhou (International Journal of Aerospace Engineering)
The atomization process of a liquid jet in supersonic crossflow with a Mach number of 1.94 was investigated numerically under the Eulerian-Lagrangian scheme. The droplet stripping process was calculated by the KH (Kelvin-Helmholtz) breakup model, and the secondary breakup due to the acceleration of shed droplets was calculated by the combination of the KH breakup model and the RT (Rayleigh-Taylor) breakup model. In our research, the existing KH-RT model was modified by optimizing the empirical constants incorporated in this model. Moreover, it was also found that the modified KH-RT breakup model is applied better to turbulent inflow of a liquid jet than laminar inflow concluded from the comparisons with experimental results. To validate the modified breakup model, three-dimensional spatial distribution and downstream distribution profiles of droplet properties of the liquid spray in the Ma=1.94 airflow were successfully predicted in our simulations. Eventually, abundant numerical cases under different operational conditions were launched to investigate the correlations of SMD (Sauter Mean Diameter) with the nozzle diameter as well as the airflow Mach number, and at the same time, modified multivariate power functions were developed to describe the correlations.